Between activism and mediatization: parties and media’s frames in the Catalan campaign of 2017 - Carratalá, Adolfo (2019)
Research on media coverage of electoral campaigns point to an increasing mediatization. This paper seeks to corroborate whether the trend also takes place in exceptional circumstances, such as those surrounding the regional elections in Catalonia in 2017. The analysis compares the frames observed in six newspapers (El País, El Mundo, La Vanguardia, El Periódico de Catalunya, Punt Avui and Ara) with those adopted by the seven political parties represented in the autonomous parliament (JuntsXCat, ERC, PSC, PP, Ciudadanos, En Comú-Podem and CUP). The results indicate that the symbolic frames characteristic of collective action were dominant in the political discourses, although the media logic once again became hegemonic in global terms.